2011
DOI: 10.1128/jb.01456-10
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Broadly Conserved Operon (RL3499-RL3502) from Rhizobium leguminosarum Biovar viciae Causes Defects in Cell Morphology and Envelope Integrity

Abstract: The bacterial cell envelope is of critical importance to the function and survival of the cell; it acts as a barrier against harmful toxins while allowing the flow of nutrients into the cell. It also serves as a point of physical contact between a bacterial cell and its host. Hence, the cell envelope of Rhizobium leguminosarum is critical to cell survival under both free-living and symbiotic conditions. Transposon mutagenesis of R. leguminosarum strain 3841 followed by a screen to isolate mutants with defectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…DNase treatment was conducted using Turbo DNase (Life Technologies). Reverse transcription reactions were carried out according to a previously described protocol (Manzon et al, 2007), with modifications described by Vanderlinde et al (2009Vanderlinde et al ( , 2011. Quantitative PCR was conducted on an Applied Biosystems StepOne Real-Time PCR System using SYBR Green PCR Master Mix (Life Technologies) as per manufacturer's instructions and using primers RL0936B and RL0936C (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…DNase treatment was conducted using Turbo DNase (Life Technologies). Reverse transcription reactions were carried out according to a previously described protocol (Manzon et al, 2007), with modifications described by Vanderlinde et al (2009Vanderlinde et al ( , 2011. Quantitative PCR was conducted on an Applied Biosystems StepOne Real-Time PCR System using SYBR Green PCR Master Mix (Life Technologies) as per manufacturer's instructions and using primers RL0936B and RL0936C (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The shared mutant phenotype of an inability to grow on complex peptide rich media suggests a possible network between these cell envelope related genes, and further experimentation is needed to identify potential interaction networks. Vanderlinde et al (2011) identified a link between the uncharacterized, broadly conserved MoxR AAA+ operon, and proper cell envelope function in R. leguminosarum. The genes in this operon are subsequently referred to as complex media growth deficient (cmdA-cmdD), based on the mutant phenotype of an inability to grow on complex peptide rich growth media.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations